ILSTS001: A polymorphic bovine microsatellite - Brezinsky, L.; Kemp, Stephen J.; Teale, A.J. (Wiley, 1992)
Source and description: An anonymous clone containing a (TG)15 microsatellite was isolated from a genomic library of an N'dama (Bos taurus) bull (designated ND7). Primers for the polymerase chain reaction (PCR) were designed to amplify the region containing this microsatellite. The size of the PCR product was shown to be polymorphic by denaturing polyacrylamide gel electrophoresis. This microsatellite was designated ILSTS001.